Indefinites in Romance and beyond - Kellert, Olga (Language Science Press, 2024)
Due to their flexibility in interpretation, the use of indefinites and other quantificational expressions is highly variable and subject to dynamic processes of language change.The present volume addresses fundamental linguistic questions about language variation and change in Romance quantificational expressions. It focuses on quantificational expressions in language varieties that have not received much attention in the previous literature, such as Old Sardinian, Argentinian Spanish, Palenquero Creole and Cabindan Portuguese, Catalan, Romanian, and others. The studies included in this volume offer new data on these processes of variation and advance theoretical discussions about language variation and change.